Peningkatan Kualitas Produk Proll Tape Di Kabupaten Jember Dengan Metode QFD dan KANO - Musmedi Didik Pudjo; Sri Wahyu Lelly Hana Setyanti; Rifa'za Amalia (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2023)
The prol tape product produced by the home industry in Jember Regency is a souvenir product typical which is very popular. Over time, the abundant availability of cassava raw materials and the high interest in buying consumers have made the rapid development of processed cassava tape products not only prol tape but other product innovatons have emerged. In the midst of the emergence of many new products, there is a need for preventive action as a measure to close the possibility of the decline in the existence of prol tape as a typical product from Jember regency and being unable to compete with other types of produstc. Effort to maintain and increase the existence of prol tape products as a distinctive product, efforts to control product quality are carried out using the quality function deployment (QFD) and Kano analysis methods to improve the quality of prol tape products by home industries in Jember regency. The sampling technique in this study used purposive sampling, based on the research results, it was obtained 9 attributes of consumer need for prol tape products produced by home industries in Jember regency, where all of its attributes in order to achieve customer satisfaction. Attributes of consumer needs consist of taste, price, texture, aroma, product durability, packaging design, product hygiene, product size, product-related information.